Presepsin and Interleukin-6 as Early Diagnostic Biomarkers of Sepsis: A Scoping Review - Putu Ngurah Pradnya Wibawa; Ni Putu Lia Juliantini; Ni Luh Putu Serly Ekayanti (Publikasi Indonesia, 2026)
Sepsis is a life-threatening medical condition with high morbidity and mortality, making early detection very important to improve patient outcomes. Conventional biomarkers such as C-reactive protein (CRP) and procalcitonin (PCT) have limitations in sensitivity and specificity, so more accurate biomarkers are needed. This study aims to analyze the role of presepsin and interleukin-6 (IL-6) as early diagnostic biomarkers of sepsis using a scoping review approach. The method used was a literature review of articles published between 2016–2026 from PubMed, ScienceDirect, and other sources based on specific inclusion and exclusion criteria. A total of 10 articles were included in this study. The results show that presepsin has high diagnostic accuracy, with AUC values ranging from 0.76 to 0.94, and is strongly associated with disease severity and patient mortality. Meanwhile, IL-6 acts as an inflammatory biomarker that significantly increases in severe cases and has good prognostic value for mortality. In addition, the combination of presepsin and IL-6 improves diagnostic accuracy and prediction compared to using a single biomarker. In conclusion, presepsin and IL-6 are complementary biomarkers in the diagnosis and prognosis of sepsis. Presepsin is more specific to bacterial infection, while IL-6 reflects the inflammatory response. Their combination has strong potential to improve early detection, risk assessment, and clinical decision-making in sepsis management.